WESTERN BALKANS CHALLENGES IN THE THIRD DECADE OF 21ST CENTURY – CASE STUDY: SERBIA AND NORTH MACEDONIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
In the methodological sense, the aim of this paper will be to reach a prediction about the potential challenges, threats and risks that the Western Balkans will face in the current decade, based on the case study of Serbia and North Macedonia. By analyzing the existing economic, political and security challenges, risks and threats facing by these two countries, as well as the European continent as a whole, the authors will try to use the method of prediction to establish to what extent the existing challenges, risks and threats will be current in the next six years, whether new ones will appear and in what intensity and what mechanisms are available to small states, such as Serbia and North Macedonia, in the process of facing and creating sustainability. In the academic sense, the contribution of this work will be to provide new understanding about what are the most effective methods in the process of recognizing the challenges facing by small states in current international relations. While, in a practical sense, the contribution will be multiple - political, economic, security - because it will provide new knowledge about potential challenges, risks and threats, as well as proposals for dealing with them.
Keywords: Challenges, Risks, Threat, Western Balkans, Serbia, North Macedonia